Why do we imitate nonsense? The underlying motivations of overimitation - Schleihauf, Hanna (2018)
Over evolutionary time, humans have come to populate the most varied environments on planet earth and somehow managed to survive. The key to this extraordinary adaptability seems to rest not exclusively in biological adaptions, but also in cultural adaptations; it is thanks to the skills and information that are transmitted to us from others (i.e. through social learning) that we manage to survive and thrive in such diverse ecologies. One special form of social learning is the imitation of causally irrelevant actions. The imitation of actions that are perceivably irrelevant to reach a certain goal seems to be unique to humans and has been termed ‘overimitation’. At first sight, copying goal irrelevant actions seems to be an inefficient learning strategy. Therefore, the legitimate question arises: Why do we do so? It has been discussed that humans overimitate either because of erroneous causal reasoning, meaning that they do not recognize demonstrated actions as being irrelevant or because of social motivations, e.g., because they want to follow a norm or want to affiliate with the demonstrator. In this thesis, I present three different studies, which tested these explanatory models. Taken together, results of these studies gave reason to think that one of these accounts standing alone is insufficient to explain the phenomenon. Therefore, I am introducing a dual-mode model for overimitation. One mode is blanket copying. Here, irrelevant actions are copied independent of contextual differences. While copying in a blanket fashion, children heuristically copy irrelevant actions without questioning their necessity. This mode is triggered by actions which involve physical contact with the testing object, because it is harder to recognize such actions as being irrelevant. The other mode is reflective copying. Here, whether or not children overimitate is dependent on their goals in a certain situation. This mode of copying is triggered by actions that do not involve physical contact with the testing object can be easily recognized as being causally irrelevant, or by observing a more efficient strategy (not including irrelevant actions). If disclosing the irrelevancy of the demonstrated actions, children’s focus is directed to an alternate efficient option to reach the desired goal. Then, they can actively decide if they would like to copy the demonstrated irrelevant actions or not. Therefore, reflected copying is context depended. According to this integrative framework, overimitation can occur in a blanket and in a reflected fashion. Thus, this model emphasizes that the same observable behavior can have different underlying motivations.